The idea of continental philosophy : a philosophical chronicle - Glendinning, Simon, 1964- (Edinburgh University Press, 2006)
The idea of Continental Philosophy has never been properly explained in philosophical terms. In this short and engaging book Simon Glendinning attempts finally to succeed where others have failed - although not by giving an account of its internal unity but by showing instead why no such account can be given. Providing a clear picture of the current state of the contemporary philosophical culture Glendinning traces the origins and development of the idea of a distinctive Continental tradition, critiquing current attempts to survey the field of contemporary philosophy.